Development of condition rating of shotcrete lining of hydroelectric power station based on condition assessment of its distresses - Usman F.; Banuar N.; Muda Z.C. (Asian Research Publishing Network, 2023)
Tunnel underground structure often exposed to an extensive deterioration especially on the tunnel lining. Water leakage is the most common distress occurred in tunnel subsequently causing other distresses to form. After providing services over years, evaluation of shotcrete tunnel lining of underground hydroelectric power station is increasing the degree of importance to ascertain its reliability. This study is conducted to generate condition rating of distress simultaneously identify how combining distresses would affect the condition of shotcrete tunnel lining rather than presenting in a single distress rating. It can be time prohibitive to conduct an assessment to identify the causes that triggered the deterioration of shotcrete using visual inspection and non-destructive test including electrical resistivity and ground penetrating radar. The results from these tests will then be analyzed using statistical analysis to determine every respective condition. There are four distresses were identified as major contribution to the deterioration of shotcrete lining involving water leakage, crack, water saturated zone and rock fractured. Based on the findings, the condition rating that has been developed able to represent more conscious descriptive meaning to each distress. Even tough when it is compared to the single parameter of assessment i.e. the water leakage, there are average different ratings from 4% to 15%. 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.